Using of Node.js in creating application based on event-driven architecture - Władysław Hrynczyszyn; Małgorzata Plechawska-Wójcik (Journal of Computer Sciences Institute, 2017)
This paper discusses a new programming method - event driven programming. This method is compared with other popular ways of implementing web services to find its weak points and discover in which areas of modern web applications it could be implemented.